Orophea chalermprakiat (Annonaceae; Malmeoideae), a new species from southern Thailand - Damthongdee, Anissara; Chanthamrong, Kithisak; Promsiri, Suwannee; Tongsang, Banchong; Jaisamut, Thani; Wiya, Chattida; Sinbumroong, Aroon; Chaowasku, Tanawat (Phytotaxa, 2024)
N/A